Ultraviolet coating for metal battery shell and preparation method of ultraviolet coating
By using the UV coating of a metal battery shell with a specific composition, the problem of insufficient cladding and adhesion on complex-shaped batteries is solved by the traditional coating process, and the blind corner coating and excellent insulation performance of complex-shaped batteries is achieved. Improves the safety performance and service life of the battery.
Patent Information
- Application Number
- CN202411644155.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-01-07
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The traditional PET blue film coating process causes an increase in the internal pressure of the battery during the charging and discharging of the battery, affecting safety performance and service life, and it is difficult to effectively cover the edges and corners of the complex shapes, reducing the durability of insulation and adhesion.
UV coating of metal battery shell composed of α-H cyano modified acrylate resin, phosphate modified acrylic resin, 50% aldehyde ketone resin, mica powder, silicon micropowder, titanium dioxide and vapor phase silica, etc., through Specific stirring steps and ingredients ratios ensure no blind corner covering and excellent insulation, high temperature and corrosion resistance.
It significantly improves the application scenarios, safety performance and service life of the battery, provides no blind spot covering for complex-shaped batteries, enhances insulation performance and adhesion, and improves the overall performance of the battery.
Smart Images

Figure BDA0005139261990000101
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coatings, and in particular to an ultraviolet coating for a metal battery shell and a preparation method thereof. Background Art
[0002] With the development of science and technology, the performance of energy storage equipment is constantly improving. Among them, the performance improvement of batteries as an important energy storage device has attracted much attention. However, due to the electrochemical reaction between the electrode materials of the battery electrolyte, the battery will generate a certain amount of heat and gas during the charging and discharging process, which may cause the increase of internal pressure of the battery, thereby affecting the safety performance and service life of the battery. Therefore, the durability of battery insulation is particularly important.
[0003] The traditional PET blue film coating process for new energy batteries is prone to bulging and decreased adhesion after long-term use, which seriously affects the durability and service life of battery insulation. In addition, with the improvement of battery technology, batteries of various complex shapes have emerged. The coating and adhesion of the corners of batteries with more complex structures in the traditional PET film coating process will also be greatly reduced. Summary of the invention
[0004] The purpose of the present invention is to provide an easy-to-use metal battery shell UV coating and a preparation method thereof in view of the deficiencies in the prior art. The coating not only has excellent durability, insulation performance, high temperature resistance and corrosion resistance, but also can cover batteries of various complex shapes without dead angles.
[0005] The purpose of the present invention is achieved through the following technical solutions:
[0006] A metal battery shell ultraviolet paint, which is composed of the following raw materials in parts by weight:
[0007] α-H cyano-modified acrylate resin 30-40 parts
[0008] Phosphate modified acrylic resin 1-5 parts
[0009] 50% aldehyde-ketone resin 5-15 parts
[0010] Isobornyl acrylate 5-15 parts
[0011] Hydroxyethyl methacrylate 10-20 parts
[0012] 2-Hydroxy-2-methyl-1-phenyl-1-propanone 3-6 parts
[0013] 2-isopropylthioxanthone 0.5-2 parts
[0014] Phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide 0.5-2 parts
[0015] Dispersant 0.1-0.5 parts
[0016] Defoaming agent 0.1-1 part
[0017] Leveling agent 0.1-0.3 parts
[0018] 8-12 parts of mica powder
[0019] Silica powder 5-15 parts
[0020] Titanium dioxide 0.5-2 parts
[0021] Fumed silica 0.1-1 part
[0022] 0.1-1 part of blue paste
[0023] Preferably, the phosphate-modified acrylic resin is Sartomer CD-9051.
[0024] Preferably, the dispersant is TEGO Dispers 652.
[0025] Preferably, the defoamer is an acrylic defoamer.
[0026] Preferably, the defoaming agent is TEGO 920 or BYK 055.
[0027] Preferably, the leveling agent is a silicone leveling agent.
[0028] Preferably, the leveling agent is BYK 300.
[0029] Preferably, the particle size of the mica powder is 50 microns to 80 microns, the particle size of the silicon powder is 10 microns to 5 microns, the particle size of the titanium dioxide is 200 nanometers to 300 nanometers, and the particle size of the fumed silica is 10 nanometers to 15 nanometers. The combination of nanometers and micrometers, the combination of different micrometer levels, and the combination of different nanometer levels make these inorganic raw materials with different particle sizes better dispersed into the system, improve the adhesion to the substrate, and further ensure that it has excellent insulation performance, high temperature resistance and corrosion resistance in different environments. At the same time, the dispersant of TEGO Dispers 652, as a special polymer dispersant, advantageously ensures the dispersion of these inorganic fillers in the three-resin system.
[0030] Preferably, the 50% aldehyde-ketone resin is obtained by uniformly mixing solid aldehyde-ketone resin and hydroxyethyl methacrylate in a mass ratio of 1:1.
[0031] A method for preparing a metal battery shell ultraviolet coating comprises the following process steps:
[0032] Step A, stirring a solid aldehyde-ketone resin and hydroxyethyl methacrylate in a mass ratio of 1:1 for 70-90 minutes to obtain a 50% aldehyde-ketone resin;
[0033] Step B, α-H cyano-modified acrylate resin, phosphate-modified acrylic resin, 50% aldehyde-ketone resin, isobornyl acrylate, hydroxyethyl methacrylate, 2-hydroxy-2-methyl-1-phenyl-1-propanone, 2-isopropylthioxanthone, phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide, dispersant, defoamer, and leveling agent are mixed and stirred for 15-25 minutes;
[0034] Step C: add mica powder, silica powder, titanium dioxide, blue slurry and fumed silica to the solution stirred in step B, and mix and stir for 30-50 minutes.
[0035] Preferably, the stirring speed in step A is 1000 rpm, the stirring speed in step B is 600 rpm, and the stirring speed in step C is a high speed of 1200 rpm.
[0036] Preferably, the fumed silica adopts the anti-settling agent AEROSIL R972 from Germany.
[0037] Beneficial effects of the present invention: The present invention uses a combination of α-H cyano-modified acrylate resin, phosphate-modified acrylic resin and 50% aldehyde-ketone resin as a base material, and is matched with inorganic fillers such as mica powder, silicon micropowder, titanium dioxide, and fumed silica, and isobornyl acrylate, hydroxyethyl methacrylate, 2-hydroxy-2-methyl-1-phenyl-1-propanone, 2-isopropylthioxanthone, phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide, dispersant, defoamer, and leveling agent, so that it has extremely strong adhesion to the substrate at the same time. The prepared coating not only has excellent insulation performance, high temperature resistance and corrosion resistance, but also can cover batteries of various complex shapes without dead angles, which can greatly improve the application scenarios, safety performance and service life of the batteries. DETAILED DESCRIPTION
[0038] The present invention is further described in conjunction with the following examples.
[0039] Example 1
[0040] A metal battery shell ultraviolet paint, which is composed of the following raw materials in parts by weight:
[0041] α-H cyano-modified acrylate resin 30 parts
[0042] Phosphate modified acrylic resin 1 part
[0043] 50% aldehyde-ketone resin 5 parts
[0044] 5 parts of Isobornyl Acrylate
[0045] 10 parts of Hydroxyethyl Methacrylate
[0046] 2-Hydroxy-2-methyl-1-phenyl-1-propanone 3 parts
[0047] 0.5 parts of 2-isopropylthioxanthone
[0048] 0.5 parts of phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide
[0049] Dispersant 0.1 part
[0050] Defoaming agent 0.1 part
[0051] 0.1 part of leveling agent
[0052] 8 parts mica powder
[0053] 5 parts of silicon powder
[0054] 0.5 parts of titanium dioxide
[0055] Fumed silica 0.1 part
[0056] 0.1 part blue paste
[0057] Wherein, the phosphate-modified acrylic resin is Sartomer CD-9051.
[0058] Wherein, the dispersant is TEGO Dispers 652.
[0059] Wherein, the defoaming agent is TEGO 920.
[0060] Wherein, the leveling agent is BYK 300.
[0061] The particle size of the mica powder is 50 microns to 80 microns, the particle size of the silicon powder is 10 microns to 5 microns, the particle size of the titanium dioxide is 200 nanometers to 300 nanometers, and the particle size of the fumed silica is 10 nanometers to 15 nanometers.
[0062] The 50% aldehyde-ketone resin is obtained by uniformly mixing solid aldehyde-ketone resin and hydroxyethyl methacrylate in a mass ratio of 1:1.
[0063] The above-mentioned method for preparing the ultraviolet coating for the metal battery shell comprises the following process steps:
[0064] Step A, stirring a solid aldehyde-ketone resin and hydroxyethyl methacrylate in a mass ratio of 1:1 for 70 minutes to obtain a 50% aldehyde-ketone resin;
[0065] Step B, α-H cyano-modified acrylate resin, phosphate-modified acrylic resin, 50% aldehyde-ketone resin, isobornyl acrylate, hydroxyethyl methacrylate, 2-hydroxy-2-methyl-1-phenyl-1-propanone, 2-isopropylthioxanthone, phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide, dispersant, defoamer, and leveling agent are mixed and stirred for 15 minutes;
[0066] Step C: Add mica powder, silicon powder, titanium dioxide, blue slurry and fumed silica to the solution stirred in step B, mix and stir for 30 minutes to obtain a metal battery shell UV coating.
[0067] The stirring speed in step A is 1000 rpm, the stirring speed in step B is 600 rpm, and the stirring speed in step C is a high speed of 1200 rpm.
[0068] Example 2
[0069] A metal battery shell ultraviolet paint, which is composed of the following raw materials in parts by weight:
[0070] α-H cyano-modified acrylate resin 35 parts
[0071] Phosphate modified acrylic resin 3 parts
[0072] 50% aldehyde ketone resin 10 parts
[0073] Isobornyl acrylate 10 parts
[0074] 15 parts of Hydroxyethyl Methacrylate
[0075] 4 parts of 2-hydroxy-2-methyl-1-phenyl-1-propanone
[0076] 2-Isopropylthioxanthone 1 part
[0077] 1 part of phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide
[0078] Dispersant 0.3 parts
[0079] 0.5 parts of defoamer
[0080] 0.2 parts of leveling agent
[0081] 9 parts mica powder
[0082] 10 parts of silicon powder
[0083] 1 part titanium dioxide
[0084] 0.5 parts of fumed silica
[0085] 0.5 parts of blue paste.
[0086] Wherein, the phosphate-modified acrylic resin is Sartomer CD-9051.
[0087] Wherein, the dispersant is TEGO Dispers 652.
[0088] Wherein, the defoaming agent is TEGO 920.
[0089] Wherein, the leveling agent is BYK 300.
[0090] The particle size of the mica powder is 50 microns to 80 microns, the particle size of the silicon powder is 10 microns to 5 microns, the particle size of the titanium dioxide is 200 nanometers to 300 nanometers, and the particle size of the fumed silica is 10 nanometers to 15 nanometers.
[0091] The 50% aldehyde-ketone resin is obtained by uniformly mixing solid aldehyde-ketone resin and hydroxyethyl methacrylate in a mass ratio of 1:1.
[0092] The above-mentioned method for preparing the ultraviolet coating for the metal battery shell comprises the following process steps:
[0093] Step A, stirring a solid aldehyde-ketone resin and hydroxyethyl methacrylate in a mass ratio of 1:1 for 80 minutes to obtain a 50% aldehyde-ketone resin;
[0094] Step B, α-H cyano-modified acrylate resin, phosphate-modified acrylic resin, 50% aldehyde-ketone resin, isobornyl acrylate, hydroxyethyl methacrylate, 2-hydroxy-2-methyl-1-phenyl-1-propanone, 2-isopropylthioxanthone, phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide, dispersant, defoamer, and leveling agent are mixed and stirred for 20 minutes;
[0095] Step C: Add mica powder, silicon powder, titanium dioxide, blue slurry and fumed silica to the solution stirred in step B, mix and stir for 40 minutes to obtain a metal battery shell UV coating.
[0096] The stirring speed in step A is 1000 rpm, the stirring speed in step B is 600 rpm, and the stirring speed in step C is a high speed of 1200 rpm.
[0097] Example 3
[0098] A metal battery shell ultraviolet paint, which is composed of the following raw materials in parts by weight:
[0099] 40 parts of α-H cyano-modified acrylate resin
[0100] Phosphate modified acrylic resin 5 parts
[0101] 50% aldehyde ketone resin 15 parts
[0102] Isobornyl acrylate 15 parts
[0103] 20 parts of Hydroxyethyl Methacrylate
[0104] 2-Hydroxy-2-methyl-1-phenyl-1-propanone 6 parts
[0105] 2-isopropylthioxanthone 2 parts
[0106] 2 parts of phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide
[0107] 5 parts of 1,6-hexanediol diacrylate
[0108] Dispersant 0.5 parts
[0109] 1 part defoamer
[0110] 0.3 parts of leveling agent
[0111] Mica powder 12 parts
[0112] 15 parts of silicon powder
[0113] 2 parts of titanium dioxide
[0114] 1 part of fumed silica
[0115] 1 part blue paste,
[0116] Wherein, the phosphate-modified acrylic resin is Sartomer CD-9051.
[0117] Wherein, the dispersant is TEGO Dispers 652.
[0118] Wherein, the defoaming agent is BYK 055.
[0119] Wherein, the leveling agent is BYK 300.
[0120] The particle size of the mica powder is 50 microns to 80 microns, the particle size of the silicon powder is 10 microns to 5 microns, the particle size of the titanium dioxide is 200 nanometers to 300 nanometers, and the particle size of the fumed silica is 10 nanometers to 15 nanometers.
[0121] The 50% aldehyde-ketone resin is obtained by uniformly mixing solid aldehyde-ketone resin and hydroxyethyl methacrylate in a mass ratio of 1:1.
[0122] The above-mentioned method for preparing the ultraviolet coating for the metal battery shell comprises the following process steps:
[0123] Step A, stirring a solid aldehyde-ketone resin and hydroxyethyl methacrylate in a mass ratio of 1:1 for 90 minutes to obtain a 50% aldehyde-ketone resin;
[0124] Step B, α-H cyano-modified acrylate resin, phosphate-modified acrylic resin, 50% aldehyde-ketone resin, 1,6-hexanediol diacrylate, isobornyl acrylate, hydroxyethyl methacrylate, 2-hydroxy-2-methyl-1-phenyl-1-propanone, 2-isopropylthioxanthone, phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide, dispersant, defoamer, and leveling agent are mixed and stirred for 25 minutes;
[0125] Step C: Add mica powder, silicon powder, titanium dioxide, blue slurry and fumed silica to the solution stirred in step B, mix and stir for 50 minutes to obtain a metal battery shell UV coating.
[0126] The stirring speed in step A is 1000 rpm, the stirring speed in step B is 600 rpm, and the stirring speed in step C is a high speed of 1200 rpm.
[0127] Comparative Example 1
[0128] The difference between Comparative Example 1 and Example 2 is that the dispersant used is the commercially available DS-165 dispersant of Tuyile.
[0129] Comparative Example 2
[0130] The difference between Comparative Example 1 and Example 2 is that only α-H cyano-modified acrylate resin is used, and phosphate-modified acrylic resin and 50% aldehyde-ketone resin are not used.
[0131] It should be clarified that the α-H-containing cyano-modified acrylate resin used in the present invention is prepared according to the following steps: Step 1: Add 66g (1 mol) of propylene glycol, 198.55g (0.83 mol) of 1,1-bis (acryloyloxymethyl) ethyl isocyanate, 7.9g of catalyst triethylamine, 0.26g of p-hydroxyanisole and 119g of anhydrous solvent N,N-dimethylformamide into a 250mL straight four-necked flask, stir evenly, and perform addition reaction at 40°C until the conversion rate of isocyanate group (NCO—) reaches 100% (wherein, the conversion rate of isocyanate group is in accordance with the national standard GBT 18446-2009 for determination), and after the reaction is complete, a crude product of a cyano-modified acrylate resin containing α-H is obtained; step 2: adding 100g of a good solvent, dichloromethane, to the crude product of the cyano-modified acrylate resin containing α-H obtained in step 1, transferring the product into a separating funnel, washing with 50g of water to remove unreacted malondicyanide, and removing the water layer; adding 50g of saturated brine for washing twice, the organic layer is clear and transparent, placing the organic layer in a 60°C water bath for reduced pressure rotary evaporation to remove the solvent (including the anhydrous solvent in step 1 and the good solvent in step 2), and finally obtaining a cyano-modified acrylate resin containing α-H.
[0132]
[0133] After the above performance tests, the samples still meet the insulation withstand voltage requirements.
[0134] In comparative example 1, the dispersant selection is unreasonable. The dispersant cannot effectively disperse the three resin matrices and fillers of α-H cyano-modified acrylate resin, phosphate-modified acrylic resin and 50% aldehyde-ketone resin, resulting in uneven product performance, decreased coating adhesion, slight cracking and other problems.
[0135] Comparative Example 2 uses only α-H cyano-modified acrylate resin, and does not use a combination of α-H cyano-modified acrylate resin, phosphate-modified acrylic resin and 50% aldehyde-ketone resin. Only one resin is used, which greatly reduces the adhesion of the substrate and causes problems such as cracking, and cannot be used for the strict requirements of metal battery casings.
[0136] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention, rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A metal battery shell UV coating, characterized in that: It is composed of the following raw materials by weight: 30-40 parts of α-H cyano-modified acrylate resin Phosphate modified acrylic resin 1-5 parts 50% aldehyde-ketone resin 5-15 parts Isobornyl acrylate 5-15 parts Hydroxyethyl methacrylate 10-20 parts 2-Hydroxy-2-methyl-1-phenyl-1-propanone 3-6 parts 2-isopropylthioxanthone 0.5-2 parts Phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide 0.5-2 parts Dispersant 0.1-0.5 parts Defoaming agent 0.1-1 part Leveling agent 0.1-0.3 parts 8-12 parts of mica powder Silica powder 5-15 parts Titanium dioxide 0.5-2 parts Fumed silica 0.1-1 part 0.1-1 part of blue paste.
2. The metal battery shell UV coating according to claim 1, characterized in that: The phosphate-modified acrylic resin is Sartomer CD-9051.
3. The metal battery shell UV coating according to claim 1, characterized in that: The dispersant is TEGO Dispers 652.
4. The metal battery shell UV coating according to claim 1, characterized in that: The defoamer is an acrylic acid defoamer.
5. The metal battery shell UV coating according to claim 1, characterized in that: The leveling agent is an organic silicon leveling agent.
6. The metal battery shell UV coating according to claim 1, characterized in that: The particle size of the mica powder is 50 microns to 80 microns, the particle size of the silicon micropowder is 10 microns to 5 microns, the particle size of the titanium dioxide is 200 nanometers to 300 nanometers, and the particle size of the fumed silica is 10 nanometers to 15 nanometers.
7. The metal battery shell UV coating according to claim 1, characterized in that: The 50% aldehyde-ketone resin is obtained by uniformly mixing solid aldehyde-ketone resin and hydroxyethyl methacrylate in a mass ratio of 1:
1.
8. The method for preparing a metal battery shell UV coating according to claim 1, characterized in that: It includes the following process steps: Step A, stirring a solid aldehyde-ketone resin and hydroxyethyl methacrylate in a mass ratio of 1:1 for 70-90 minutes to obtain a 50% aldehyde-ketone resin; Step B, α-H cyano-modified acrylate resin, phosphate-modified acrylic resin, 50% aldehyde-ketone resin, isobornyl acrylate, hydroxyethyl methacrylate, 2-hydroxy-2-methyl-1-phenyl-1-propanone, 2-isopropylthioxanthone, phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide, dispersant, defoamer, and leveling agent are mixed and stirred for 15-25 minutes; Step C: Add mica powder, silicon powder, titanium dioxide, blue slurry and fumed silica to the solution stirred in step B, mix and stir for 30-50 minutes to obtain a metal battery shell UV coating.
9. The method for preparing a metal battery casing UV coating according to claim 8, characterized in that: The stirring speed in step A is 1000 rpm, the stirring speed in step B is 600 rpm, and the stirring speed in step C is a high speed of 1200 rpm.
Citation Information
Patent Citations
UV (ultraviolet) primer composition attached to melamine board and preparation method of UV primer composition
CN106519919A
UV cured paint used for surface of aluminum alloy and preparation method thereof
CN106947393A
Filling-type UV colorant and preparation method thereof
CN110256905A
Alpha-H-containing cyano modified acrylate resin and preparation method and application thereof
CN114085165A
Radiation-curing solid-color matte skin-touch coating
CN116694224A
Cited By
Ultraviolet curing anticorrosive paint as well as preparation method and application thereof
CN120775470A